United Kingdom oil and gas fields : commemorative millennium volume - Gluyas, J. G.; Hichens, H. M. (Geological Society ; Distributor, AAPG Bookstore, 2003)
This book is divided into nine parts covering the major petroleum provinces both offshore and onshore United Kingdom, from the Gas Basin in the southern North Sea to the Viking Graben in the northern North Sea, from the Atlantic Frontier to the Irish Sea and from the Wessex Basin to the East Midlands. Each part contains a reference map showing field locations. The introductory chapters reveal the stories behind the major plays and discoveries therein, and their tectonic and stratigraphic framework.
Keywords: Petroleum -- Geology -- North Sea.; Petroleum -- Geology -- Great Britain.; Petroleum in submerged lands -- North Sea.; Petroleum in submerged lands -- Great Britain.; Gas fields -- North Sea.; Gas fields -- Great Britain.; elektronické knihy; electronic books